ANALISIS PENGARUH KETERSEDIAAN QRIS DALAM TRANSAKSI JUAL BELI BAGI UMKM KETINTANG - Nawang Fatmala; Jihan Zahidah Imtinan B. (Cahaya Ilmu Bangsa, 2024)
This study aims to analyze the effect of the availability of Quick Response Indonesian Standard (QRIS) in buying and selling transactions for Micro, Small and Medium Enterprises (MSMEs) in Ketintang. QRIS as a non-cash payment system in Indonesia has made it easier for MSME players to make transactions. With the increasing number of QRIS users, it is expected to increase the volume and nominal transactions, as well as MSME revenues. The research method used in this research is quantitative method through questionnaires involving MSME players in the Ketintang area, Surabaya. The results showed that the use of QRIS not only facilitates the payment process, but also increases consumer confidence and expands market reach for MSMEs.